Quantitative assessment of the contributions of inorganic and organic components of Hertsa drinking mineral water in its effect on the neuro-endocrine-immune complex and metabolism in female rats - Zukow, Walery; Savytskyi, Ivan; Popovych, Dariya; Kovalchuk, Halyna; Ponomarenko, Ruslan (Journal of Education, Health and Sport, 2026)
Background and aim. Our attention was drawn to the drinking mineral water from the Hertsa field (Chernivtsi oblast’, Ukraine) due to its unique combination of salts, trace elements and organic substances. The aim of this study was to quantitatively assess the contributions of inorganic and organic components of this water in its effect on the neuro-endocrine-immune complex and metabolism in female rats. Material and methods. The experiment carried out at 40 female rats Wistar line. 10 animals remained intact with free access to tap daily water, 10 formed a control group, whose members loaded with same daily water (3 mL/200g) once for 6 days, while 10 rats of the next group loaded with native water from the Hertsa field (HN) or its artificial saline analogue (HASA). The day after the completion of the treating course in all rats assessed the state of neuro-endocrine-immune complex and metabolism. Results. The registered variables were screened to identify those in which at least two groups differed significantly. As a result of discriminant analysis, only 12 variables were included in the model, while the remaining 6 were left out of the model as carriers of duplicate/redundant discriminant information. It was found that the procedure of loading animals with plain water is not physiologically neutral, but is accompanied by changes in a number of variables as a manifestation of chronic aversive stress (increased levels of testosterone, aldosterone, Na/K serum ratio, glycemia, catalase activity in combination with decreased levels of PTH, calcium, Ca/P serum ratio, potassium, chloriduria, natriuria, osmolarity urine, NK lymphocytes as well as the thickness of the medullary zone of adrenal glands. Taking into account this fact, it has been stated that both inorganic (salts & trace elements) and organic substances of HN and HASA reduce, eliminate or even reverse stressor effects as well as initiate a number of others, in particular a significant increase in glomerular filtration rate.